A biomechanical comparison of conventional classifications of bowling action-types in junior fast bowlers. Issue 10 (18th May 2020) - Schaefer, Andrew; Ferdinands, Rene E. D.; O'Dwyer, Nicholas; Edwards, Suzi
ABSTRACT: Fast bowling is categorised into four action types: side-on, front-on, semi-open and mixed; however, little biomechanical comparison exists between action types in junior fast bowlers. This study investigated whether there are significant differences between action-type mechanics in junior fast bowlers. Three-dimensional kinematic and kinetic analyses were completed on 60 junior male fast bowlers bowling a five-over spell. Mixed-design factorial analyses of variance were used to test for differences between action-type groups across the phases of the bowling action. One kinetic difference was observed between groups, with a higher vertical ground reaction force loading rate during the front-foot contact phase in mixed and front-on compared to semi-open bowlers; no other significant group differences in joint loading occurred. Significant kinematic differences were observed between the front-on, semi-open and mixed action types during the front-foot contact phase for the elbow and trunk. Significant kinematic differences were also present for the ankle, T12-L1, elbow, trunk and pelvis during the back-foot phase. Overall, most differences in action types for junior fast bowlers occurred during the back-foot contact phase, particularly trunk rotation and T12-L1 joint angles/ranges of motion, where after similar movement patterns were utilized across groups during the front-foot contact phase.